SCREENER, an educational game for teaching the Drug Discovery and Development process - Noël,F. (2021)
Although the use of games as an educational strategy is an important current trend, there is practically no option available for training people on the Drug Discovery and Development (DDD) process. To fill this gap, we designed “SCREENER”, a science game that is intended to be educational, but also challenging and interesting enough to ensure player engagement. Our main target audience is students of postgraduate programs in pharmacology, medicinal chemistry, pharmacy, and medicine. This game could also be of interest to the pharmaceutical industry and regulatory and patent agencies for training new employees. We discuss the creation of SCREENER, a hybrid of board and card games, and present its components with some examples of cards and resources, as well as the dynamics of the game. SCREENER mimics the process of drug discovery and development from validating a target to registering the new drug with the regulatory agency, and can be played individually (self-learning) or with the help of a monitor who assists up to six players/teams. Briefly, 29 task cards categorized in four major areas (efficacy, safety, pharmacokinetics, and pharmaceutical development) must be purchased sequentially. Classic characteristics of games such as decision making and challenge have been incorporated. More in-depth information on the tasks and technical terms is available through QR codes. The vagaries of the DDD process are mimicked by the bonus/setback cards. The evaluation of our first test with students is presented and supports the usefulness of this new tool.